2016
DOI: 10.1136/bmjopen-2015-010377
|View full text |Cite
|
Sign up to set email alerts
|

Access to Transplantation and Transplant Outcome Measures (ATTOM): study protocol of a UK wide, in-depth, prospective cohort analysis

Abstract: IntroductionThere is significant intercentre variability in access to renal transplantation in the UK due to poorly understood factors. The overarching aims of this study are to improve equity of access to kidney and kidney–pancreas transplantation across the UK and to optimise organ allocation to maximise the benefit and cost-effectiveness of transplantation.Methods and analysis6844 patients aged 18–75 years starting dialysis and/or receiving a transplant together with matched patients active on the transplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 45 publications
0
33
0
Order By: Relevance
“…A full description of the ATTOM study methods and protocol has been reported previously [10]. As part of the ATTOM study, incident kidney transplant recipients were recruited at the time of transplantation from all 23 UK renal transplant centres.…”
Section: Methodsmentioning
confidence: 99%
“…A full description of the ATTOM study methods and protocol has been reported previously [10]. As part of the ATTOM study, incident kidney transplant recipients were recruited at the time of transplantation from all 23 UK renal transplant centres.…”
Section: Methodsmentioning
confidence: 99%
“…Centre differences in outcomes of transplantation are explored later in this chapter. A large national study (access to Transplant and Transplant Outcome Measures (ATTOM)) is currently investigating differences in access to and outcomes of renal transplantation [11]. The work has already identified significant age, ethnicity, socio-economic and geographic disparities in the utilisation of living kidney donor transplants in the UK [12].…”
Section: Resultsmentioning
confidence: 99%
“…There are a number of potential explanations for these inconsistencies, including geographical differences in access to renal transplantation in the UK. This has previously been analysed in detail by the UKRR [2] and is currently the focus of a large national study (access to Transplant and Transplant Outcome Measures (ATTOM)) [3].…”
Section: Resultsmentioning
confidence: 99%